Sea ice perturbations in aquaplanet simulations: isolating the physical climate responses from model interventions - M R England; N Feldl; I Eisenman (Environmental Research: Climate)
Comprehensive climate model simulations with perturbed sea ice covers have been extensively used to assess the impact of future sea ice loss, suggesting substantial climate changes both in the high latitudes and beyond. However, previous work using an idealized energy balance model calls into question the methods that are used to perturb sea ice cover, demonstrating a consistent overestimate of the surface warming due to sea ice loss, while the large complexity gap between the idealized and comprehensive models makes the implications of this result unclear. To bridge this gap we have performed simulations with a new implementation of the CESM2 model in a slab ocean aquaplanet configuration coupled with thermodynamic sea ice, which is able to capture the realistic seasonal characteristics of polar climate change. Using this model setup, we perform a suite of experiments to systematically quantify the spurious climate responses associated with melting sea ice without a CO _2 forcing. We find that using the sea ice ghost flux method overestimates many aspects of the climate response by 10%–20%, including the polar warming, the mini global warming signal and the increase in both precipitation and evaporation. The location of the latitudinal band of heating applied to melt the sea ice relative to the midlatitude jet is important for determining where the midlatitude circulation response is overestimated. This work advances our ability to isolate the true climate response to sea ice loss, and provides a framework for conducting coupled sea ice loss simulations absent the spurious impacts from the addition of artificial heating.